Mengembangkan Jiwa Kewirausahaan Ibu Rumah Tangga Nelayan - Muhammad Azis; Fajriani Azis (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract. This Community Partnership Program (PKM) partner is a housewife in Boriappaka Village, Bungoro District, Pangkep Regency. The problems are: (1) partners lack enthusiasm in entrepreneurship, (2) partners do not understand how to develop an entrepreneurial spirit. The method used is: interactive lectures. The results achieved are (1) partners are more enthusiastic about entrepreneurship in more creative ways, and (2) partners can understand how to foster an entrepreneurial spirit.